Stage and grade determination of periodontitis accompanied by systemic conditions and diseases according to American Academy of Periodontology 2017 Classification: Study at Dental Hospital, Faculty of Dentistry, Universitas Indonesia - Ette SS. Tadjoeddin; Nabila P. Dewi; Yuniarti Soeroso; Benso Sulijaya; Natalina Natalina (Journal of Dentomaxillofacial Science, 2021)
Objective: Periodontitis is an inflammatory disease of the supporting tissues of the teeth caused by specific microorganisms, resulting in decay of the teeth and damaging of supporting tissues. Systemic conditions and increasing age will affect the periodontal tissue due to amongst others changes in the immune defense system. The classification for periodontal diseases used today is the 1999 American Academy of Periodontology (AAP) classification.  The latest development was in 2017, when the AAP published a new classification that classifies periodontitis based on stage and grade and is the classification that is widely used today. Research on determining the stage and grade of periodontitis using the 2017 AAP classification is still very rare in Indonesia.Material and Methods: In this study, a cross sectional analytical descriptive approach was used to determine the stage and grade of periodontitis according to the classification of periodontal disease based on the 2017 AAP in relation to the age of patients with systemic conditions and diseases. A total of 331 medical records from patients treated at the RSKGM FKG UI in the 2017 – 2019 visit were researched.Results: The results have shown that the highest stage and grade in all research subjects was stage III grade C, , this stage and grade was found in subjects who smoke. Different results were found in research subjects with Diabetes Mellitus or Hypertension namely stage III grade B.Conclusion: Patients with hypertension without any systemic disease and non smoking should be advised to request a test for diabetes mellitus.